BEHAVIOR OF HYBRID REINFORCED CONCRETE BEAMS COMBINING REACTIVE POWDER CONCRETE AND VARYING YTPES OF LIGHTWEIGHT CONCRETE - G. Abtan, Yaarub; T. Jaber, Hind (Journal of Engineering and Sustainable Development, 2016)
The main objective of this research was studied the flexure behavior of hybrid reinforced concrete beams combining reactive powder concrete (RPC) and lightweight concrete (LWC). The experimental work consists of casting and testing in flexure 12 simply supported reinforced concrete beams. The dimensions of (12) beams were geometrically similar, having rectangular cross-section, of dimensions (125×200×1600) mm. Lightweight concrete was used in tension layer and reactive powder concrete was used in compression layer for all hybrid concrete beams. The main variables were type of concrete (LWC and RPC), thicknesses of RPC layer (hR =0, 50 and 100) mm, volumetric steel ratios (Vf =1%) in LWC and type of LWC (porecilenite aggregate, polystyrene and sawdust). The results showed that the characteristic strength (first and ultimate loads) was increased when the thickness of RPC layer was increased; this increased percentage were (7-100) % and (32-133) % respectively for first cracking loads and ultimate loads. In addition to that, these parameters were decreased the values of deflection from (1-17) %. However that it can be seen from the experimental results, the concrete with steel fiber and porecilenite had more effective than the concrete with other types of aggregate (sawdust and polystyrene). Also the concrete with porecilenite type reflected more number of cracks than sawdust and polystyrene, respectively. All beams failed by flexure mode without any shear cracks which achieved by yielding of tensile steel in the tension zone. Also, for all hybrid beams, the slip was absent between the concrete layers.